HEALTH RELATED QUALITY OF LIFE AND PERCEIVED SOCIAL SUPPORT IN PATIENTS WITH DIAGNOSIS OF PULMONARY TUBERCULOSIS - Vinaccia Alpi, Stefano; Margarita Quiceno, Japcy; Fernández, Hamilton; Elena Pérez, Beatriz; Olga Sánchez, María; Londoño, Amanda (Anales de Psicología / Annals of Psychology, 2007)
The following investigation show the results of a study on the evaluation of the health-related quality of life and the social support per-ceived in 60 patients with diagnosis of tuberculosis pulmonary between the 18 to 70 years of age of both genders enrolled in the control program and prevention of tuberculosis of Metrosalud de Antioquia, Colombia. In order to evaluate the quality of life Questionnaire SF36 was used and the functional social support was evaluated by means of Questionnaire DUKE-UNK. Indicating that the sample had a quality of good life and very little support or social endorsement. In general there was discharge reliability in all the study with an alpha of Cronbach superior to .80.